MRI Brain Changes After Marathon Running: Results of the Berlin Beat of Running Study - Herm, Juliane; Haeusler, Karl Georg; Kunze, Claudia; Krüll, Matthias; Brechtel, Lars; Lock, Jürgen; Heuschmann, Peter U.; Haverkamp, Wilhelm; Heekeren, Hauke; Liman, Thomas; Endres, Matthias; Fiebach, Jochen B.; Jungehulsing, Gerhard Jan (International Journal of Sports Medicine, 2019)
Several studies report neurological complications such as brain injury induced by ischemia or edema following exhaustive endurance sport. We aimed to detect the frequency of acute brain lesions after a marathon race. In the prospective observational Berlin Beat of Running study, 110 experienced endurance athletes underwent 3-Tesla brain MRI exams 2–3 days prior and within 2 days after a marathon run. MRI results were compared to an age- and sex-matched control group of 68 non-athletes, including the “Age-Related White Matter Changes” (ARWMC) scale to assess white matter lesions (WML) in the brain. 108 athletes (median age 48 years, 24% female, 8% with hypertension; 0% with diabetes) completed the race. No athlete reported neurological deficits, but a single acute ischemic lesion was detected in diffusion-weighted MRI after the race in one athlete. No other acute brain lesions compared to prior MRI were found. An ARWMC score ≥4 was found in 15% of athletes and 12% of non-athletic controls (p=0.7). Chronic ischemic lesions were not found in athletes but in four controls (6%) (p=0.02). In conclusion, acute ischemic brain lesions may be found in endurance runners. Every seventh endurance athlete and every ninth control showed evidence for substantial white matter lesions.
Keywords: marathon; athletes; edema; stroke; ischemic brain lesions; magnetic resonance imaging